2021
DOI: 10.1111/jdi.13511
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel‐like factor 15 regulates fuel switching between glucose and fatty acids in brown adipocytes

Abstract: Aims/Introduction Brown adipose tissue (BAT) utilizes large amounts of fuel for thermogenesis, but the mechanism by which fuel substrates are switched in response to changes in energy status is poorly understood. We have now investigated the role of Kruppel‐like factor 15 (KLF15), a transcription factor expressed at a high level in adipose tissue, in the regulation of fuel utilization in BAT. Materials and Methods Depletion or overexpression of KLF15 in HB2 differentiated brown adipocytes was achieved by adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(34 reference statements)
5
4
0
Order By: Relevance
“…Notably, thermogenesis pathways were among the topmost enriched pathways as well, supporting observations that body temperature decreases with fasting ( Figure 1 C) ( Chatamra et al., 1984 ). The RNA-seq data are concordant with past studies that have shown decreased BAT Pdk4 transcription, PDK4 activity, and glucose oxidation in fasting with a concurrent increase in lipid metabolism gene expression ( Nabatame et al., 2021 ). These findings also suggest that fasting induces a nutrient switch in BAT like that seen in liver and muscle, where nutrient consumption is downregulated to preserve circulating glucose for glucose obligate organs, such as the brain.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Notably, thermogenesis pathways were among the topmost enriched pathways as well, supporting observations that body temperature decreases with fasting ( Figure 1 C) ( Chatamra et al., 1984 ). The RNA-seq data are concordant with past studies that have shown decreased BAT Pdk4 transcription, PDK4 activity, and glucose oxidation in fasting with a concurrent increase in lipid metabolism gene expression ( Nabatame et al., 2021 ). These findings also suggest that fasting induces a nutrient switch in BAT like that seen in liver and muscle, where nutrient consumption is downregulated to preserve circulating glucose for glucose obligate organs, such as the brain.…”
Section: Resultssupporting
confidence: 88%
“…Yet, it can also robustly partake in FA synthesis, storage, and release much like WAT ( Festuccia et al., 2011 ; Yu et al., 2002 ). Here, we found that concordant with past studies, BAT Klf15 expression is upregulated in fasting conditions like that in liver and muscle ( Marmol et al., 2020 ; Nabatame et al., 2021 ). Furthermore, KLF15 exhibits a similar circadian rhythmicity across BAT, liver, and muscle, which corresponds with times of relative nutrient abundance and deficit, suggesting a similar function in energy mobilization and utilization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study demonstrated a diurnal variation in fat oxidation, but not in carbohydrate oxidation, in the High-BAT group, suggesting that BAT utilizes fatty acids more preferentially in the morning than in the evening. Recently, we [ 42 ] reported a role of Kruppel-like factor 15 (KLF15), a transcription factor highly expressed in adipose tissue, in the regulation of fuel switching between glucose and fatty acids in response to changes in energy status in BAT. It is also known that KLF15 expression exhibits a clear circadian rhythm in several peripheral organs and coordinates diurnal variations of plasma levels and catabolism of amino acids including branched-chain amino acids (BCAA) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%